Factors in Rejecting Covid-19 Vaccine in Indonesia: A Systematic Review - Indana Zulva, Dewi; Eka Sari, Jayanti Dian; Syahrul Ramadan; Afan Alfayad; Anjali Putri Agustin; Syifaul Lailiyah (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: The primary approach to mitigating the Covid-19 epidemic is the implementation of community-wide vaccination initiatives. Nevertheless, a significant obstacle is the widespread refusal to accept the administration of the Covid-19 vaccination. Aims: This study aims to ascertain the determinants behind vaccination hesitancy towards the Covid-19 vaccine in Indonesia. Methods: The research methodology used in this work involves a systematic review approach, specifically using a literature study technique. The literature review used the Google Scholar, Neliti, and Garuda Jurnal databases, focusing on publications published between 2020 and 2021. The literature study search included inclusion criteria encompassing studies involving human subjects, open access availability, and publication in national journals. Results: 38 related publications were identified by the keywords. There were 9 studies subjected to analysis in the final process. Conclusion: The rejection of vaccines in Indonesia can be attributed to various factors, including the prevalence of COVID-19 hoaxes and conspiracies, the level of public knowledge, attitudes, and perceptions towards vaccines, doubts and concerns regarding their efficacy, potential side effects, safety, and compliance with halal standards, as well as the influence of individuals in close relationships.